Grundlagen der biologischen Bekämpfung. - Šcepetilnikova, V. A. (Contributions to Entomology = Beiträge zur Entomologie, 1963)
There are generalized the results of research work on principles of biological control obtained by collaborators of the Laboratory of Biological Control (Institute of Plant Protection, Leningrad).